ADHD and the QbTest: Diagnostic Validity of QbTest. Issue 11 (September 2018) - Hult, Nicklas; Kadesjö, Josefin; Kadesjö, Björn; Gillberg, Christopher; Billstedt, Eva
Objective: We assess the diagnostic accuracy of the QbTest, which measures the cardinal symptoms of ADHD.Method: The study group comprised 182 children (mean age about 10 years), of whom 124 had ADHD and 58 had other clinical diagnosis of which 81% had ASD.Results: Only QbTest parameters for inattention and hyperactivity differentiated between ADHD and other clinical diagnoses at the p ≤ .01 level, not for measures of impulsivity. Sensitivity ranged from 47% to 67% and specificity from 72% to 84%. Positive predictive value ranged from 41% to 86%, and negative predictive value from 43% to 86%. Area under the curve varied from .70 to .80.Conclusion: The ability of the individual QbTest parameters to identify ADHD was moderate. The test's ability to discriminate between ADHD subtypes was unsatisfactory.